Upaya Meningkatkan Kompetensi Guru dalam Pembelajaran Melalui Program Micro Teaching di SMP Negeri 4 Pasarkemis Kabupaten Tangerang Tahun Pelajaran 2021/2022 - Sugiyanta Sugiyanta (Lembaga Pengembangan Kinerja Dosen, 2022)
Based on the researcher's experience while teaching in Class IX.E of SMP Negeri 3 Pasarkemis, some of the students in Class IX.E did not participate properly during Indonesian language lessons. The learning process is less effective due to the lack of student activity in reading Indonesian language lesson material, the lack of student activity in expressing opinions during the lesson. Lack of student activity in answering questions from the teacher. Students are less interested in taking Indonesian language lessons. So many students divert their attention, such as chatting with their classmates, drawing, and are not enthusiastic when listening to the teacher explaining the lesson. This is caused by the teacher's model or way of explaining the lesson being too monotonous so that students do not pay enough attention to the teacher during the lesson, and the learning process will not go well.